Vaping on Instagram: cloud chasing, hand checks and product placement. Issue 5 (22nd September 2016) - Chu, Kar-Hai; Allem, Jon-Patrick; Cruz, Tess Boley; Unger, Jennifer B
Abstract : Introduction: This study documented images posted on Instagram of electronic cigarettes (e-cigarette) and vaping (activity associated with e-cigarette use). Although e-cigarettes have been studied on Twitter, few studies have focused on Instagram, despite having 500 million users. Instagram's emphasis on images warranted investigation of e-cigarettes, as past tobacco industry strategies demonstrated that images could be used to mislead in advertisements, or normalise tobacco-related behaviours. Findings should prove informative to tobacco control policies in the future. Methods: 3 months of publicly available data were collected from Instagram, including images and associated metadata (n=2208). Themes of images were classified as (1) activity, for example, a person blowing vapour; (2) product, for example, a personal photo of an e-cigarette device; (3) advertisement ; (4) text, for example, 'meme' or image containing mostly text and (5) other . User endorsement (likes) of each type of image was recorded. Caption text was analysed to explore different trends in vaping and e-cigarette-related text. Results: Analyses found that advertisement -themed images were most common (29%), followed by product (28%), and activity (18%). Likes were more likely to accompany activity and product -themed images compared with advertisement or text -themed images (p<0.01). Vaping-related text greatly outnumbered e-cigarette-related text in the image captions. Conclusions: Instagram affords its users the ability to post images of e-cigarette-related behaviours and gives advertisers the opportunity to display their product. Future research should incorporate novel data streams to improve public health surveillance, survey development and educational campaigns.